ASSESSMENT OF THE FINANCIAL AND ECONOMIC SECURITY OF A CRITICAL INFRASTRUCTURE ENTERPRISE - ONYSHCHENKO, Svitlana; MASLII, Oleksandra; DRIBNA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article substantiates the importance of ensuring the financial and economic security of a critical infrastructure enterprise in wartime conditions. It was established that it serves as a guarantee of "survival" and the basis for maintaining a stable position of the business entity in wartime. The higher the stability of the enterprise, the lower the risk of the influence of external and internal factors on its economic and financial security and activity as a whole.The current crisis situation in the world and in Ukraine requires enterprises to quickly respond to external and internal challenges that can both positively and negatively affect the efficiency of the enterprise. The aggressor's troops are attacking Ukrainian cities, shelling the civilian population, infrastructure, residential buildings, kindergartens, schools, colleges, and universities. As a result of the russian war, a large part of the energy infrastructure, which is critical for Ukraine, was damaged. Therefore, it is timely and relevant to assess the financial and economic security of a critical infrastructure enterprise.The article analyses the activities of JSC "POLTAVAOBLENERGO". The level of its financial and economic security is determined. Taking into account the realities of today, it should be noted that the financial condition of JSC "POLTAVAOBLENERGO" can be characterized as difficult, crisis. A high probability of bankruptcy, a financial crisis, and the presence of "sick" items in the balance sheet are a sign of a low level of financial and economic security of the studied critical infrastructure enterprise.The scientific and applied principles of qualitative and quantitative factors that determine the peculiarities of the safety-oriented activity of the enterprise have been revealed. The main threats that destabilize the activity of the critical infrastructure enterprise have been systematized. Measures are proposed that will contribute to increasing the level of financial and economic security of JSC "POLTAVAOBLENERGO".
Keywords: financial and economic security; critical infrastructure; internal and external threats; indicators